Probabilistic performance assessment of seismically excited buildings with semi-active fluid viscous dampers - Ali Asghar Naderi; Sina Bkhshinezhad; Shahrokh Rezaei (Numerical Methods in Civil Engineering)
This paper presents a procedure to assess the probabilistic performance of the semi-active fluid viscous dampers (SAFVDs) utilized in seismically excited buildings. Some efficient on-off semi-active control algorithms based on motion towards or away from equilibrium, sky-hook, and ground-hook have been considered to determine the variable damping in each time step. The probabilistic relationship between intensity measure (IM) and seismic demand of the building has been estimated based on cloud analysis. A linear regression analysis has been employed to calculate the probabilistic demand parameters. A three-story nonlinear shear-type building equipped with SAFVDs has been adopted for the numerical example. The building has been subjected to a set of 20 actual earthquke records with the probability of occurrence of 10% in 50 years for the site of interest. The probabilistic performance of the nonlinear building equipped with SAFVDs has been assessed in terms of demand and fragility curves. The results indicate the effectiveness of the SAFVD systems in mitigating the fragility and enhancing the safety of the building. Particularly, a fragility reduction of about 51% is achieved at the immediate occupancy (IO) performance level using the SAFVD system.